Expressions of Future Time in Newspaper Writing - Kristan, Jan (Univerzita Pardubice, 2022)
The aim of this work is to analyse the use of the future time in English in newspaper writing. Firstly, the thesis defines the individual structures used to express future time. Secondly, a brief description of the journalistic style is given. In the practical part, the results of the analysis are presented and interpreted and the context in which individual structures are used is described.
Vyjadřování futura v žurnalistickém stylu
Keywords: Futurum; čas; noviny; žurnalistický styl; Future time; tense; newspapers; newspaper writing